PENGEMBAGAN BAHAN AJAR EDUMAT (EDUKASI MATEMATIKA) BERBASIS DIGITAL PADA MATERI BANGUN DATAR SEBAGAI PENDAMPING MUATAN MATEMATIKA SD - Farihatun Nisa'; Nuhyal Ulia; Rida Fironika Kusumadewi (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2021)
This research focuses on developing interactive teaching materials based on digital flat shape materials. The lack of availability of teaching materials and the use of technology occurs at the elementary school level, especially in the Mathematical content of flat shape materials. The purpose of this study was to determine the characteristics and appropriateness of Edumat teaching materials for Mathematics content of grade IV SD. The method used is research and development (R&D). This development research uses the Borg and Gall model which has been modified by Sugiyono into 7 stages. Based on this, the research results obtained include: (1) Product design stage which includes potentials and problems, data collection, media making tools and product design. (2) Product results, at this stage, produce digital-based teaching materials with the format (.apk). (3) The results of product trials which include design validation that get an average score of 0.86, the criteria